Taxonomic revision of the genus Jekelius López-Colón, 1989 (Coleoptera: Geotrupidae) in the Levant region - Sommer, David; Hillert, Oliver; Král, David (Zootaxa, 2025)
The genus Jekelius López-Colón, 1989 in the Levant region is revised. Jekelius (Jekelius) bargylus Sommer, Hillert & Král, sp. nov., from Syria, Jekelius (Jekelius) impavidus Sommer, Hillert & Král, sp. nov., from Israel, Jekelius (Jekelius) luciae Sommer, Hillert & Král, sp. nov., from Jordan, and Jekelius (Jekelius) pertinax Sommer, Hillert & Král, sp. nov., from Lebanon and Syria, are described, illustrated, and compared with its congeners. Jekelius (Jekelius) syriacus (Jekel, 1866), revised status, is elevated from subspecies to the species status. Lectotype for Geotrupes (Thorectes) laevigatus var. syriacus Jekel, 1866 is designated. Distribution of all these species is summarized and mapped.